2013
DOI: 10.1038/ki.2013.110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevelamer treatment on cardiovascular abnormalities in mice with chronic renal failure

Abstract: Elevated serum phosphate and fibroblast growth factor 23 (FGF23) levels are associated with cardiovascular disease (CVD) in patients with chronic renal failure (CRF). The phosphate-binder sevelamer has been shown to decrease both phosphate and FGF23, but limited data indicate that sevelamer improves CRF-related CVD, such as diastolic dysfunction, left ventricular hypertrophy (LVH), and aortic stiffness. To gain additional information, we measured the effects of sevelamer on CVD in a murine model of CRF. Groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 47 publications
0
43
0
6
Order By: Relevance
“…We subsequently used the same animal model to test the effect of sevelamer administration on CKD-related CV abnormalities. 56 In line with the observed decrease in both hyperphosphatemia and FGF23 levels, sevelamer treatment reduced ED, aortic stiffness and left ventricular diastolic dysfunction and thus prevented the progression of left ventricular hypertrophy. We reported that sevelamer treatment is also associated with a decreased expression of proteins related to myocardial hypertrophy compared with CKD placebo mice.…”
Section: Animal Studiesmentioning
confidence: 60%
“…We subsequently used the same animal model to test the effect of sevelamer administration on CKD-related CV abnormalities. 56 In line with the observed decrease in both hyperphosphatemia and FGF23 levels, sevelamer treatment reduced ED, aortic stiffness and left ventricular diastolic dysfunction and thus prevented the progression of left ventricular hypertrophy. We reported that sevelamer treatment is also associated with a decreased expression of proteins related to myocardial hypertrophy compared with CKD placebo mice.…”
Section: Animal Studiesmentioning
confidence: 60%
“…Even data from animal CKD models are unpersuasive, particularly in early progressive models of disease. Some studies either show a lack of response to phosphate restriction altogether (80) or relate improvement in cardiovascular function to changes in phosphate rather than FGF23 (103). While extreme, phosphate restriction (zero phosphate diet), however, has been associated with a paradoxical increase in plasma FGF23 (104).…”
Section: Dietary Phosphate Restriction and Oral Phosphate Bindersmentioning
confidence: 99%
“…To achieve the LPS binding in the gut, we used sevelamer, a LPS-sequestering, phosphate-binding drug that has been shown to reduce plasma LPS levels in patients with chronic kidney disease (15), in which the levels of microbial translocation are increased due to uremia-associated gut damage (16,17). We hypothesized that early in vivo blockade of microbial translocation in SIVsab-infected PTMs would result in the control of chronic immune activation/inflammation.…”
Section: Introductionmentioning
confidence: 99%